Design of RNAi hairpins for mutation-specific silencing of ataxin-7 and correction of a SCA7 phenotype. - Janine Scholefield; L Jacquie Greenberg; Marc S Weinberg; Patrick B Arbuthnot; Amr Abdelgany; Matthew J A Wood (PLoS ONE)
Spinocerebellar ataxia type 7 is a polyglutamine disorder caused by an expanded CAG repeat mutation that results in neurodegeneration. Since no treatment exists for this chronic disease, novel therapies such post-transcriptional RNA interference-based gene silencing are under investigation, in particular those that might enable constitutive and tissue-specific silencing, such as expressed hairpins. Given that this method of silencing can be abolished by the presence of nucleotide mismatches against the target RNA, we sought to identify expressed RNA hairpins selective for silencing the mutant ataxin-7 transcript using a linked SNP. By targeting both short and full-length tagged ataxin-7 sequences, we show that mutation-specific selectivity can be obtained with single nucleotide mismatches to the wild-type RNA target incorporated 3' to the centre of the active strand of short hairpin RNAs. The activity of the most effective short hairpin RNA incorporating the nucleotide mismatch at position 16 was further studied in a heterozygous ataxin-7 disease model, demonstrating significantly reduced levels of toxic mutant ataxin-7 protein with decreased mutant protein aggregation and retention of normal wild-type protein in a non-aggregated diffuse cellular distribution. Allele-specific mutant ataxin7 silencing was also obtained with the use of primary microRNA mimics, the most highly effective construct also harbouring the single nucleotide mismatch at position 16, corroborating our earlier findings. Our data provide understanding of RNA interference guide strand anatomy optimised for the allele-specific silencing of a polyglutamine mutation linked SNP and give a basis for the use of allele-specific RNA interference as a viable therapeutic approach for spinocerebellar ataxia 7.